Depression and anxiety among nurses during the COVID-19 pandemic: Longitudinal results over 2 years from the multicentre VOICE–EgePan study - Grasmann, Lenja; Morawa, Eva; Adler, Werner; Schug, Caterina; Borho, Andrea; Geiser, Franziska; Beschoner, Petra; Jerg-Bretzke, Lucia; Albus, Christian; Weidner, Kerstin; Mogwitz, Sabine; Baranowski, Andreas M.; et al. (Journal of Clinical Nursing, 2024)
Aims: To examine symptoms of depression and generalised anxiety among nurses over 2 years during the pandemic and compare them to the general population. Background: The COVID-19 pandemic has led to a significant increase in mental stress among the population worldwide. Nursing staff have been identified as being under remarkable strain. Design: A multicentre prospective longitudinal study. Methods: Symptoms of depression and generalised anxiety in 507 nurses were examined at four different time points (T1: April–July 2020, T2: November 2020–January 2021, T3: May–July 2021, T4: February–May 2022). Results were compared with values of the German general population, presence of gender-specific differences was analysed and frequencies of clinically relevant levels of depression and anxiety were determined. Results: Throughout the study (T1–T4), a significant increase in depressive and anxiety symptoms was observed. At all four measurement time points, nurses showed significantly higher prevalence for depression and anxiety compared to the German general population. No significant gender differences were found. Frequencies for probable depression and generalised anxiety disorder among nurses were: 21.6% and 18.5% (T1), 31.4% and 29.2% (T2), 29.5% and 26.2% (T3), 33.7% and 26.4% (T4). Conclusion: During the pandemic, symptoms of depression and generalised anxiety among nurses increased significantly and remained elevated. Their symptom levels were permanently higher than in the general population. These findings strongly suggest that the circumstances of the pandemic severely affected nurses´ mental health. Relevance to Clinical Practice: The COVID-19 pandemic caused a great mental strain on caregivers. This study was able to demonstrate the significant increase in depression and anxiety among nurses during the pandemic. It highlights the urgent need for prevention, screening and support systems in hospitals. Implications for the Profession: Supportive programmes and preventive services should be developed, not least to prevent the growing shortage of nurses in the health care systems. Reporting Method: The study adhered to relevant EQUATOR guidelines. The STROBE checklist for cohort study was used as the reporting method. Patient Contribution: Five hundred and seven nurses completed the questionnaire and provided data for analysis. Trial and Protocol Registration: The study was registered with the German Clinical Trials Register (https://drks.de/search/en) under the following ID: DRKS00021268.
CRIS-Team Scopus Importer:2024-04-19
Keywords: anxiety; COVID-19; depression; health care workers; longitudinal; mental health; nurses; pandemic; prospective